2021
DOI: 10.1002/pds.5354
|View full text |Cite
|
Sign up to set email alerts
|

Off‐label drug use in neonates and infants in Spain: A five‐year observational study

Abstract: Objectives: To provide information about the off-label rate of all drug prescriptions in neonates and infants up to 1 year in Spain. Also, to analyse the off-label prescription of medicines under current practice in this age group according to different evidence sources.Study design: A five-year (2015-2019) exploratory observational study about off-label prescription in neonates and infants (0 to 1 year) at primary health care in Spain. All drug prescriptions in this age group were analysed and classified acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…There are several caveats to evaluating NHP product use in terms of “off-label” and “unlabeled” since these terms are not universally defined, and NHPs are notoriously difficult to classify due to country-specific variations in their regulatory approval [ 23 ]. Having said this, our rates for off-label use are of the same magnitude as other developed countries [ 2 , 24 , 25 , 26 , 27 ]. Off-label medication treatment of children is well described in the hospital setting, involving up to 65% of prescription drugs in pediatric and neonatal units [ 26 ].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…There are several caveats to evaluating NHP product use in terms of “off-label” and “unlabeled” since these terms are not universally defined, and NHPs are notoriously difficult to classify due to country-specific variations in their regulatory approval [ 23 ]. Having said this, our rates for off-label use are of the same magnitude as other developed countries [ 2 , 24 , 25 , 26 , 27 ]. Off-label medication treatment of children is well described in the hospital setting, involving up to 65% of prescription drugs in pediatric and neonatal units [ 26 ].…”
Section: Discussionmentioning
confidence: 55%
“…Off-label medication treatment of children is well described in the hospital setting, involving up to 65% of prescription drugs in pediatric and neonatal units [ 26 ]. Fewer studies—none in Canada—have investigated this issue from an outpatient perspective [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings do not apply to other settings, such as in hospitals, where off-label prescribing is likely to be higher. 30,31 Off-label prescribing has also been shown to be high in newborns, especially in intensive care units 32,33 ; however, we were unable to explore this population due to the lack of exact date of birth and the incomplete capture of medicine use in hospitals. More in-depth studies of this population in the Australian context are warranted.…”
Section: Limitations Of the Datamentioning
confidence: 99%
“…Several studies have been conducted in an attempt to quantify the off-label prescription rate in neonates. These include a 5-year observational study from Spain by Lizano-Díez et al [4], which demonstrated that 34.10% of drugs prescribed to neonates over a period of 2 years were prescribed off-label. A prospective cohort study by Costa et al [5] examined the prevalence of neonates administered off-label and unlicensed drugs in a neonatal intensive care unit (NICU) in Brazil and found that 96.4% of neonates and 100% of extremely preterm neonates or extremely low birth weight neonates were exposed to off-label drugs, while 66.8%, 76.7% and 75.7% were exposed to unlicensed drugs, respectively.…”
Section: Introduction 1drug Information In Neonatesmentioning
confidence: 99%